2016
DOI: 10.7554/elife.18458
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic control of gene regulatory logic by seemingly redundant transcription factors

Abstract: Many transcription factors co-express with their homologs to regulate identical target genes, however the advantages of such redundancies remain elusive. Using single-cell imaging and microfluidics, we study the yeast general stress response transcription factor Msn2 and its seemingly redundant homolog Msn4. We find that gene regulation by these two factors is analogous to logic gate systems. Target genes with fast activation kinetics can be fully induced by either factor, behaving as an 'OR' gate. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…Indeed, TFs can regulate genes by transient bursts of nuclear localization in response to external signals (Cai et al 2008; Hao & O’Shea 2012; Liu et al 2015). Moreover, the timing of colocalization bursts by different regulators may be a means to combinatorially control transcription (Lin et al 2015; Akhavan Aghdam et al 2016). Under the recruitment model, combinatorially acting TFs must be colocalized to the nucleus at the same time in order to co-recruit one another and/or the transcriptional machinery.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, TFs can regulate genes by transient bursts of nuclear localization in response to external signals (Cai et al 2008; Hao & O’Shea 2012; Liu et al 2015). Moreover, the timing of colocalization bursts by different regulators may be a means to combinatorially control transcription (Lin et al 2015; Akhavan Aghdam et al 2016). Under the recruitment model, combinatorially acting TFs must be colocalized to the nucleus at the same time in order to co-recruit one another and/or the transcriptional machinery.…”
Section: Resultsmentioning
confidence: 99%
“…The cytoplasm and the nucleus of single cells were identified by thresholding the phase image and the iRFP nuclear marker. For each individual cell, the mean fluorescence intensities for the cytoplasm and the nucleus were then quantified and smoothed separately, using a custom MATLAB code, as described in previous studies (AkhavanAghdam et al, ; Hansen, Hao, & O'Shea, ; Hao, Budnik, Gunawardena, & O'Shea, ; Hao & O'Shea, ). The ratio of the cytoplasmic to nuclear intensity (KTR C/N ratio) was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Kss1-9xMyc-tagged strains were generated by homologous recombination of a PCR-amplified 9xMyc cassette harbouring a resistance gene to hygromycin B from plasmid pYM20 (pYM-9xMyc-hphNT1; Janke et al, 2004) at the C-terminus of the KSS1 open reading frame (ORF). Nhp6a-iRFP-tagged strains were generated by homologous recombination of a PCR-amplified iRFP-HIS3 cassette from plasmid pKT-iRFP-HIS (AkhavanAghdam, Sinha, Tabbaa, & Hao, 2016). The kinase translocation reporter (KTR) for Fus3 was integrated at the TDH3 promoter following SnaBI digestion of plasmid pRS305 pTDH3-KTR (Li, Roberts, AkhavanAghdam, & Hao, 2017).…”
Section: Strains and Plasmidsmentioning
confidence: 99%
“…When tested in conditions where both factors are expressed to equivalent amounts, the two factors induced the same set of genes ( Figure 4C, S6). Since a previous study 39 which followed stress gene induction using fluorescence reporters, indicated some differences in individual targets dependence on Msn2,4, we examined specifically the genes reported to be differently regulated. However, none of these genes showed any difference in their Msn2,4 dependency in any of the 6 conditions for which we performed tight time-course measurements ( Figure S7).…”
Section: Msn2 and Msn4 Induce The Same Set Of Target Genesmentioning
confidence: 99%